PENGARUH LAMA DAN SUHU PENGASAPAN DENGAN MENGGUNAKAN METODE PENGASAPAN PANAS TERHADAP MUTU IKAN LELE ASAP - Sulfiani, Sulfiani; Sukainah, Andi; Mustarin, Amirah (Universitas Negeri Makassar, 2017)
This research aims to determine the time and temperature of fumigation using hot fumigation method to tind the quality of smoke eatfish. This research used a completely random design that consist of two treatments; 4 hours and 6 hours and temperature 400C and 500C. The parameters of this research werethe content of water, protein, ash, and hedonic value of smoke catfish. The results of this research showed that the best treatment was 6 hours in temperature 500C by content of waterÂ 8.73% , protein 24.63%, and ash 13.36%.